ANALYSIS OF STUDENT’ MISTAKES IN SOLVING PROBLEM ON PYTHAGORAS THEOREM AT SMP NEGERI PALU - Mustamin Idris; Yuyun Selasti; Anggraini Anggraini; Gandung Sugita (USN Kolaka, 2024)
The purpose of this study is: to describe students' mistakes in solving Pythagorean Theorem problems at SMP Negeri 9 Palu using qualitative research methods. The subjects of this study were 3 students who were taken from 26 students who had studied the Pythagorean theorem. The selection of research subjects took into account: (1) these students made more mistakes; (2) different errors; (3) represent mistakes made by other students; (4) students' ability to communicate well and (5) recommendations from math teachers. Data collection techniques used are assignments and interviews. The analysis in this study uses Gagne's theory. The results of this study indicate that some of the mistakes students experienced in solving Pythagorean theorem problems were: (1) Subjects EN and SF made mistakes in using the Pythagorean theorem formula; (2) Subjects EN and SF made mistakes in writing mathematical symbols; (3) Subjects EN, MR and SF made mistakes in determining the hypotenuse of a right triangle; (4) Subjects EN, MR and SF made the mistake of not using the rank; (5) Subjects EN, MR and SF made mistakes in not writing down work procedures completely and accurately and (6) Subjects SF made mistakes in not doing calculations correctly.